2006
DOI: 10.1271/bbb.70.1200
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bifunctional α-Amylase/Subtilisin Inhibitor: Cloning and Characterization of the Recombinant Inhibitor Expressed inEscherichia coli

Abstract: The complete nucleotide sequences of the cDNA and its gene that encode a bifunctional alpha-amylase/subtilisin inhibitor of rice (Oryza sativa L.) (RASI) were analyzed. RASI cDNA (939 bp) encoded a 200-residue polypeptide with a molecular mass of 21,417 Da, including a signal peptide of 22 amino acids. Sequence comparison and phylogenetic analysis showed that RASI is closely related to alpha-amylase/subtilisin inhibitors from barley and wheat. RASI was found to be expressed only in seeds, suggesting that it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Svendsen et al (1986) have cloned and expressed a 19.8 kDa barley protein (BASI) that inhibits α-amylase and the protease subtilisin. Yamasaki et al (2006) have cloned a 21.4 kDa of bi-functional α-amylase/subtilisin inhibitor from rice (RASI). The recombinant inhibitor has strong inhibitory activity towards subtilisin and weak inhibitory activity towards α-amylase.…”
Section: Discussionmentioning
confidence: 99%
“…Svendsen et al (1986) have cloned and expressed a 19.8 kDa barley protein (BASI) that inhibits α-amylase and the protease subtilisin. Yamasaki et al (2006) have cloned a 21.4 kDa of bi-functional α-amylase/subtilisin inhibitor from rice (RASI). The recombinant inhibitor has strong inhibitory activity towards subtilisin and weak inhibitory activity towards α-amylase.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of alpha-amylase was determined according to Yamasaki et al (2006) with some modifications. The material was homogenized in K-Pi buffer (as for protein extraction) and the supernatant was used as a crude enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, disease/defense-related proteins such as glycosylated polypeptides, α-amylase/subtilisin inhibitors and chitinases were enhanced in abundance in wheat roots during flood condition (Kong et al, 2010). Among these, α-amylase/subtilisin inhibitors function in defense against micro-organisms (Yamasaki et al, 2006) and chitinase is involved in a defense mechanism against pathogens as well as abiotic stresses (Shibuya and Minami, 2001). Higher abundance of these proteins in the root thus indicated that molecular processes such as protein folding and degradation are involved in plant adaptive responses toward unfavorable environmental condition.…”
Section: Proteomics Overview On Abiotic Stress Responses In Plant Rootsmentioning
confidence: 99%